Neural networks and robotic microneedles enable autonomous extraction of plant metabolites. Issue 3 (16th May 2021) - Bae, Hansol; Paludan, Magnus; Knoblauch, Jan; Jensen, Kaare H.
Abstract: Plant metabolites comprise a wide range of extremely important chemicals. In many cases, like savory spices, they combine distinctive functional properties—deterrence against herbivory—with an unmistakable flavor. Others have remarkable therapeutic qualities, for instance, the malaria drug artemisinin, or mechanical properties, for example natural rubber. We present a breakthrough in plant metabolite extraction technology. Using a neural network, we teach a computer how to recognize metabolite-rich cells of the herbal plant rosemary ( Rosmarinus officinalis ) and automatically extract the chemicals using a microrobot while leaving the rest of the plant undisturbed. Our approach obviates the need for chemical and mechanical separation and enables the extraction of plant metabolites that currently lack proper methods for efficient biomass use. Computer code required to train the neural network, identify regions of interest, and control the micromanipulator is available as part of the Supplementary Material . Abstract : A method for autonomous extraction from individual cells using a micromanipulator is developed and applied to glandular trichomes.